Lung function test in children with left-to-right shunt congenital heart disease - Carolina Kurniawan; Indah Kartika Murni; Sasmito Nugroho; Noormanto Noormanto; Roni Naning (Paediatrica Indonesiana, 2018)
Background Increased pulmonary blood flow may lead to abnormal lung function in children with left-to-right (L to R) shunt congenital heart disease. This condition has been linked to considerable mortality and morbidity, including reduced lung function. Objective To assess for lung function abnormality in children with L to R shunt congenital heart disease. Methods We conducted a cross-sectional study involving children aged 5-18 years and diagnosed with L to R shunt congenital heart disease at Dr. Sardjito Hospital from March to May 2017. Subjects underwent spirometry tests to measure forced expiratory volume-1 (FEV-1), forced vital capacity (FVC), and forced expiratory volume-1 (FEV-1)/forced vital capacity (FVC). Results Of 61 eligible subjects, 30 (49.2%) children had atrial septal defect (ASD), 25 (41%) children had ventricular septal defect (VSD), and 6 (9.8%) children had patent ductus arteriosus (PDA). Spirometry revealed lung function abnormalities in 37 (60.7%) children. Restrictive lung function was documented in 21/37 children, obstructive lung function in 11/37 children, and mixed pattern of lung function abnormality in 5/37 children. Pulmonary hypertension was found in 21 children. There was no significant difference in lung function among children with and without pulmonary hypertension (P=0.072). Conclusion Abnormal lung function is prevalent in 60.7% of children with L to R shunt congenital heart disease, of which restrictive lung function is the most common. There was no significant difference in lung function among children with and without pulmonary hypertension.